Daya antibakteri ekstrak kulit apel manalagi (Malus sylvestris (L.) Mill) terhadap pertumbuhan Streptococcus sanguinis - Made Prashanti Pradayani; Ni Kadek Fiora Rena Pertiwi; IGA Dyah Ambarawati (School of Dentistry Faculty of Medicine Udayana University, 2021)
Introduction: Streptococcus sanguinis is one of the gram-positive bacteria that causes dental and oral diseases that play a role in the process of dental plaque formation. Manalagi apples are fruits that are very easy to find, the fruit peel contains antibacterial compounds derived from polyphenols including catechins, quercetin, phloridzin and chlorogenic acid. The use of apple manalagi peel extract can be used as an antibacterial natural product especially in the oral cavity. The purpose of this study was to assess the inhibition of Manalagi apple peel extract (Malus sylvestris (L.) Mill) against the growth of Streptococcus sanguinis. Method: This type of research is experimental with Post Test Only Control Group Design. There are 5 treatment groups, extract concentration of 25%, 50%, 100%, positive control with chlorhexidine 0.2%, and negative control with aquades. The antibacterial test method uses the disc diffusion method by saturating each extract into disc paper which then diffuses into the media to contain Streptococcus sanguinis bacteria. Result: Phytochemical test results of manalagi apple peel extract showed saponin, fenol, terpenoid, flavonoid and alkaloid. The antibacterial activity test result showed of zone diameter at a concentration of 25% is 0 mm, a concentration of 50% 7.3 mm, a concentration of 100% 7.5 mm, positive control 14.3 mm and a negative control 0 mm. Data analysis used the Kruskal Wallis tests and showed p< 0,05. Conclusion: The conclusion of this study is manalagi apple peel extract at a concentration of 50% and 100% has an antibacterial effect on the growth of Streptococcus sanguinis. Latar Belakang: Streptococcus sanguinis merupakan salah satu bakteri gram positif penyebab penyakit gigi dan mulut yang berperan dalam proses pembentukan plak gigi. Buah apel manalagi adalah buah yang sangat mudah ditemukan, kulit buahnya mengandung senyawa antibakteri turunan polifenol diantaranya katekin, kuersetin, phloridzin, serta asam klorogenik. Penggunaan ekstrak kulit apel manalagi dapat digunakan sebagai produk alami antibakteri terutama dalam rongga mulut. Penelitian ini bertujuan guna menilai daya hambat ekstrak kulit apelmanalagi (Malus sylvestris (L.) Mill) terhadap pertumbuhan Streptococcus sanguinis. Metode: Jenis penelitian eksperimental, dengan Post Test Only Control Group Design. Terdapat 5 kelompok perlakuan yaitu, konsentrasi ekstrak 25%,50%,100%, kontrol positif dengan chlorhexidine 0,2% serta kontrol negatif dengan aquades. Metode uji antibakteri menggunakan metode difusi cakram dengan menjenuhkan masing-masing ekstrak ke dalam kertas cakram yang kemudian berdifusi ke media agar yang berisi bakteri Streptococcus sanguinis. Hasil: Uji fitokimia ekstrak kulit apel manalagi memperlihatkan adanya senyawa saponin, fenol, terpenoid, flavonoid, dan alkaloid. Hasil rerata diameter zona hambat pada konsentrasi 25% ialah 0 mm, konsentrasi 50% 7,3 mm, konsentrasi 100% 7,5 mm, kontrol positif 14,3 mm dan kontrol negatif 0 mm. Analisis data menggunakan uji Kruskal Wallis menunjukkan nilai p<0,05. Kesimpulan: Ekstrak kulit apel manalagi pada konsentrasi 50% dan 100% memiliki daya antibakteri terhadap pertumbuhan Streptococcus sanguinis.